Narrative theory in conservation : change and living buildings - Walter, Nigel (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Narrative Theory in Conservation engages with conservation, heritage studies and architecture approaches to historic buildings, offering a synthesis of the best of each, and demonstrating that conservation is capable of developing a complementary, but distinct, theoretical position of its own. Tracing the ideas behind the development of modern conservation in the West, and considering the challenges presented by non-Western practice, the book engages with the premodern understanding of innovation within tradition, and frames historic buildings as intergenerational, communal, ongoing narratives. Redefining the appropriate object of conservation, it suggests a practice of conserving the questions that animate and energize local cultures, rather than only those instantiated answers that expert opinion has declared canonical. Proposing a narrative approach to historic buildings, the book provides a distinctive new theoretical foundation for conservation, and a basis for a more equal dialogue with other disciplines concerned with the historic environment. Narrative Theory in Conservation articulates a coherent theoretical position for conservation that addresses the urgent question of how historic buildings that remain in use should respond to change. As such, the book should be of great interest to academics, researchers and postgraduate students from the fields of conservation, heritage studies and architecture"--
Context : people and change in conservation -- Modernity : conservation, discontinuity and the past -- People : community, language and power -- Tradition : change and continuity -- Narrative : time, history and what happens next -- Application : the narrative approach to conservation -- Conclusion : conservation 'as if people mattered'.
OCLC-licensed vendor bibliographic record.
Keywords: Historic buildings -- Conservation and restoration; Architecture and society; Historic preservation -- Social aspects; Historic preservation -- Philosophy; ARCHITECTURE / Historic Preservation